Solid breast tumors phantom emulating oxy and deoxyhemoglobin concentrations for near infrared imaging - María Victoria Waks-Serra; Demián Augusto Vera; Nicolás Abel Carbone; Héctor Alfredo García; Pamela Alejandra Pardini; Juan Antonio Pomarico; Daniela Inés Iriarte (PLoS ONE, 2025)
Significance: Continuous-wave near-infrared spectroscopy (CW-NIRS) is a valuable, inexpensive and non-invasive tool for complementary diagnose breast cancer. The use of phantoms has proven to be a very powerful way to evaluate different experimental approaches as well as to test possible diagnostics equipment. The phantoms developed in this work can properly emulate either benign or malignant tumors and, in contrast to those constructed with actual biological chromophores, require no special storage, being thus stable in time. Aim: In this work we study the feasibility of employing two artificial absorbents as a replacement for oxygenated and deoxygenated hemoglobin concentrations in breast tumors, allowing discrimination benign from malignant tumors in CW transmittance NIRS experiments. Approach: Tumor phantoms were made of epoxy resin containing two kinds of absorbents to emulate the absorption curves of the hemoglobins in concentrations that reproduce those of benign and malignant tumors (fibroadenoma and adenocarcinoma respectively). CW transmittance NIRS experiments were carried out to evaluate the approach which was also compared with Monte Carlo (MC) simulations. Results: Results show that the constructed tumor phantoms are feasible to reproduce the desired targets. Additionally, the retrieved concentrations agree with the proposed ones. Thus, it is possible to construct a phantom containing inclusions emulating a fibroadenoma and/or an adenocarcinoma suitable for testing mammography algorithms or equipment. Conclusions: We have successfully designed, constructed, and validated tumor phantoms emulating both benign and malignant breast tumors. The transmittance experiments carried out agree very well with MC simulations. In addition, it was possible to obtain a map of absorbent concentrations recovered from the diffuse imaging experiments.